ANALISIS KEBAHASAAN TRADISI MAKKOBAR SEBAGAI NILAI-NILAI PENDIDIKAN KARAKTER PADA UPACARA ADAT PERKAWINAN MASYARAKAT BATAK ANGKOLA: kebahasaan - Dina Syahfitri; Winda Sari; Erwina Azizah Hasibuan; Fita Delia Gultom (Edukasi Lingua Sastra, 2022)
Indonesia is country rich traditional customs, one of them makkobar tradition Batak Angkola community in Tabagsel. Makkobar tradition is often carried out at traditional wedding ceremonies. The purpose research is analyze language Makkobar as character education values traditional marriage ceremony Batak Angkola community. This research uses qualitative methods and descriptively. The analysis is three: 1).Linguistic analysis of makkobar tradition inthe martahi godang session as value character education, namely 29 opening words of makkobar by 7 source emphasize the value of character education respecting and Out of the 32 words mangalusi by 7sources, they emphasized the value of democratic character education.2).Linguistic analysis of makkobar tradition inthe mangalehen mangan session as values ​​of character education, namely: 23poda words by 6sources emphasized the value of friendly character education.3). Linguistic analysis of makkobar tradition inthe pasahat boru sessionas the values character education, namely introduction to adaboru line, thereare 25words of poda by 6 sources emphasize value of socialcare character education. And inthe introduction to alaklahi line, thereare 32 poda words by 6 sources who emphasize value of friendly character education. and mangalusi represented by bou contained 5 poda words, namely religious, honesty, tolerance, love for homeland and respect.